The Clinical Evaluation of Serum WS Biotin, a Novel Encapsulated Form of D‐Biotin With Improved Water Solubility, for Anti‐Hair Shedding Applications. A Prospective Single‐Arm, Nonrandomized, Pretest−Posttest Study - David González Fernández; Shaher Duchi; Lucía Fernández Gómez; Teresa León Sala; Akram Hajuj; Danit Molho; Nadeen Abo Saada; Daniel Molina Martínez; Alejandro Pérez‐Fernández; Danny Goldstein (Health Science Reports)
ABSTRACT Background and Aims Hair shedding is an aesthetic concern increasingly being addressed by the cosmetic industry. Biotin has long been used as an oral supplement to promote hair growth and strength, without solid evidence supporting this practice. Recently, we have shown that encapsulated biotin has promising bioactivity in hair growth‐related parameters in vitro. For this reason, this study aimed at evaluating the association between the application of Serum WS Biotin, a novel water‐soluble form of D‐Biotin, and hair shedding and strength, after topical application for 3 months. Methods A cohort of 22 volunteers with moderate to excessive hair shedding was subjected to daily application of Serum WS Biotin for 3 months. Baseline and follow‐up (Days 30, 60, and 90 after the application started) Modified Pull Test (MPT), Modified Hair Wash Test (MHWT), and phototrichogrametry measurements were conducted on the study cohort. Results Hairs pulled through MPT were reduced by 43.0% at D30, 56.0% at D60, and 76.1% at D90. Regarding MHWT, the number of vellus hairs (< 3 cm) was significantly reduced by 90.6% at D30, 67.0% at D60, and 74.8% at D90. Concomitantly, pulled hairs > 3 cm significantly diminished by 69.4% at D60 and 60.0% at D90. Contrarily, a significant increase of 227.5% was recorded at D30. Last, the hair thickness median rose significantly by 7.5% at D30, 10.6% at D60, and 7.6% at D90. Consistently, hair thickness mean was nonsignificantly increased by 4.6% at D30, 18.0% at D60, and 17.8% at D90. Interestingly, results also provided a nonstatistically significant improvement in hair mass by 3.2% at D30 and 10.4% at D90. Conclusion The 3‐month application of Serum WS Biotin displays anti‐hair shedding and strengthening capabilities, showing good cutaneous acceptability and compatibility.